Overexpressing CCW12 in Saccharomyces cerevisiae enables highly efficient ethanol production from lignocellulose hydrolysates. (October 2021) - Kong, Meilin; Li, Xiaowei; Li, Tongtong; Zhao, Xuebing; Jin, Mingjie; Zhou, Xin; Gu, Hanqi; Mrša, Vladimir; Xiao, Wei; Cao, Limin
Graphical abstract: Highlights: Ethanol yield of CCW12 OE was around 0.503 g/g total sugars in simulated hydrolysate. Contributions of gene CCW12 on ethanol yields were evaluated in various hydrolysates. CCW12 OE with high ethanol yield was achieved in corncob hydrolysate only within 12 h. Improved acetate tolerance of CCW12 OE was identified via TEM observation. Abstract: A Saccharomyces cerevisiae strain CCW12 OE was constructed by overexpressing CCW12 in a previously reported strain WXY70 harboring six xylose utilization genes. CCW12 OE produced an optimal ethanol yield of 98.8% theoretical value within 48 h in a simulated corn stover hydrolysate. CCW12 OE  was comprehensively evaluated for ethanol production in Miscanthus, maize and corncob hydrolysates, among which a 96.1% theoretical value was achieved within 12 h in corncob hydrolysates. Under normal growth conditions, CCW12 OE did not display altered cell morphology; however, in the presence of acetate, CCW12 OE maintained relatively intact cell structure and increased cell wall thickness by nearly 50%, while WXY70 had abnormal cell morphology and reduced cell wall thickness by nearly 50%. Besides, CCW12 OE had higher fermentation capacity than that of WXY70 in undetoxified and detoxified hydrolysates with both aerobic and anaerobic conditions, demonstrating that CCW12 overexpression alone exhibits improved stress resistance and better fermentation performance.